(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background. A valid instrument to measure the bullying in primary schools is needed to determine the actual conditions. Aim. This study aimed to adapt the BYS-S questionnaire and psychometric evaluation with a cultural approach. Method. This psychometric testing applies the cross cultural adaptation method which consists of five translation stages. Item validity was analyzed by Rank-Spearman (r) and Cronbach’s alpha (?) correlation test and followed by tests to obtain discriminatory power and difficulty level for each item. Result. The results showed that the items had a high level of validity and reliability with some discriminatory items and the difficulty level of each item was very good. Discriminated and difficulty items in the form and impact on bullying victims were higher than the bullies and bystanders. Conclusion. BYS-S questionnaire Bahasa Indonesia’s version can be considered valid and reliable and has excellent discriminatory and difficulty power.